Self-powered sensor integration system based on thorn-like polyaniline composites for smart home applications. (15th December 2022) - Zhao, Youwei; Li, Xiang; Hou, Ningle; Yuan, Tian; Huang, Shuhong; Li, Ling; Li, Xiaoting; Zhang, Wenming
Abstract: Self-powered sensors that can continuously and accurately detect physiological signals without an external power source are the key technology to realize wearable electronic devices as the next generation of sensors. However, the manufacturing of self-supporting electronic systems based on versatile materials is still facing significant challenges. Herein, we introduce a new one-body strategy, zinc ion battery (ZIB) is the technology of flexible sensor energy supply, the technology uses a rechargeable solid-state zinc ion battery with multiple charging modes as the energy supply unit (405.07 mAh g −1 ), and the electrode material is used as the sensitive layer of the flexible pressure sensor, which greatly improves the sensitivity (S=5.64 *10 5 kPa −1 ) of the pressure sensor through layer assembly technology. This pressure sensor possesses good flexibility, fast response/recovery time (60.0/80.0 ms), stable long-term response, excellent cycle stability (8000 times) and wide pressure detection (50 Pa-70, 000 Pa). We believe that the design of the self-powered sensor integration system will open up a new and versatile platform for the next generation of autonomous power electronics in smart home applications. Graphical Abstract: ga1 Highlights: Reports a real-time monitoring system with an integrated self-powered wearable sensing system. The system has a high-sensitivity sensor (5.64 *10 5 kPa −1 ) that can be monitored continuously. PANI is the core material used, with reversible redox capability and oxygen reduction activity. The system realizes wireless and continuous data transmission by ITO technology.